Nonsignaling extracellular spacer regulates tumor antigen selectivity of CAR T cells - Kelly T. Kennewick; Yukiko Yamaguchi; Jackson Gibson; Ethan A. Gerdts; Brook Jeang; Dileshni Tilakawardane; John P. Murad; Wen-Chung Chang; Sarah L. Wright; Michalina S. Thiel; Stephen J. Forman; Lawrence A. Stern; et al. (Molecular Therapy: Oncology)
Advancing chimeric antigen receptor (CAR)-engineered T cells for the treatment of solid tumors is a major focus in the field of cellular immunotherapy. Several hurdles have hindered similar CAR T cell clinical responses in solid tumors as seen in hematological malignancies. These challenges include on-target off-tumor toxicities, which have inspired efforts to optimize CARs for improved tumor antigen selectivity and overall safety. We recently developed a CAR T cell therapy targeting prostate stem cell antigen (PSCA) for prostate and pancreatic cancers, showing improved preclinical antitumor activity and T cell persistence by optimizing the intracellular co-stimulatory domain. Similar studies were undertaken to optimize HER2-directed CAR T cells with modifications to the intracellular co-stimulatory domain for selective targeting of breast cancer brain metastasis. In the present study, we evaluate various nonsignaling extracellular spacers in these CARs to further improve tumor antigen selectivity. Our findings suggest that length and structure of the extracellular spacer can dictate the ability of CARs to selectively target tumor cells with high antigen density, while sparing cells with low antigen density. This study contributes to CAR construct design considerations and expands our knowledge of tuning solid tumor CAR T cell therapies for improved safety and efficacy.